PELAKSANAAN PENDIDIKAN AGAMA PADA SMA YPK DIASPORA KOTA JAYAPURA* - Asnandar Abu Bakar (Jurnal Dialog, 2014)
This paper aims at investigating course inovations in religious education developed by SMA YPK Diaspora for non Christian students. In this school, these students were obliged to take Christianity as the religious subject. Course innovation developed by the teachers was based on inquiry approach where the learning was focused on the students’ needs; and that the students were required to be active in developing and exploring the learning materials. This approach was supported by some methods, such as: lecturing, discussion, and practical works so that the students could interact directly with the teachers. By this means, students comprehended the subject better. To explore the students’ competence and to build a good communication with the teachers, a continuous educative interaction was developed so that non-Christian students were motivated to study Christianity. This was to equip the students with sufficient knowledge to build inter-religious harmony. The evaluation results of the religious subject indicated that non-Christian students obtained satisfactory grades in the subject, implying that they were able to comprehend Christianity well.